DEVELOPMENT OF LKPD USING A PROBLEM BASED LEARNING MODEL BASED ON ETHNOMATHEMATICS ON CIRCLE MATERIAL SMP CLASS VIII - Marsella, Melsa; Lusiana, Lusiana; Rohana, Rohana (Universitas Tanjungpura, 2024)
The aim of this development research is to produce LKPD using the Ethnomathematics-based Problem Based Learning Model in SMP Class VIII on Circle Material that is valid, practical, and has potential effects. The ethnomathematics used in this research is the architecture of the Abdul Kadim grand mosque. Development research was carried out using the ADDIE model which consists of 5 stages, namely: Analysis, Design, Development, Implementation, Evaluation. This research was tested on students in class VIII of SMP Negeri 1 Sekayu, the sample in this study was limited to students in class VIII.2 of SMP Negeri 1 Sekayu. The data collection instruments used were observations, validation sheets, questionnaires and tests. The analysis technique used is quantitative analysis. So, the results of this research show that the Student Worksheet (LKPD) developed is in the very valid category based on the validity aspect with an average percentage score of 89.7%, based on the practicality aspect with an average percentage score of 84% categorized as very practical , as well as the potential effect on student learning outcomes of 88.8%.